Experimenting with the King of France - Abrusán, Márta; Szendröi, Kriszta (Proceedings of the Amsterdam Colloquium, 2011)
Definite descriptions with reference failure have been argued to give rise to different truth-value intuitions depending on the local linguistic context in which they appear. We conducted an experiment to investigate these alleged differences. We have found that pragmatic strategies dependent on verification and topicalization, suggested in the context of trivalent theories, indeed play a role in people’s subjective judgments. Overall however we think that our find ings are best explained by combining these pragmatic strategies with an approach that assumes that definite descriptions have a bivalent semantics, as well as a pragmatic presupposition attached to them. We also suggest that the verification of a sentence –where possible – proceeds through a pivot constituent, and that this concept is relevant for the proper description of how speakers understand semantic meaning.